Comic–Based Health Education and Its Effect on Children’s Knowledge of Sexual Violence Prevention at SDN Joglo 08 Pagi - Winancy Winancy; Karin Sanaya; Yulia Sari (jitek, 2026)
Sexual violence is the most common form of child abuse in Indonesia. Sexual violence against children has a negative impact that can damage the development process and future of children, so it is necessary to provide health education about sexual violence in the right way. One way that can be used is by utilizing digital media through e-comics. The purpose of this study was to determine the effect of health education using e-comics media on children's knowledge about efforts to prevent sexual violence. This study is a quantitative research model using a pre experimental research design with a one group pretest-posttest design. This study used primary data with a sample of 42 students in grade 6 of Sekolah Dasar Negeri (SDN)/Public Elementary School Joglo 08 Pagi with a sampling technique using simple random sampling. And data analysis using a parametric test (paired t-test). The results of this study stated that there was a significant difference in the level of children's knowledge before is mean value 46.88, and std deviation 9.541. after is mean value 84.43, std deviation 9.034 and after being given intervention through e-comic media about efforts to prevent sexual violence against children with a p value of 0.001 <0.05.